Assessing the Economic Feasibility of Short-Rotation Woody Crops in Florida - Matthew Langholtz; Douglas R. Carter; Donald L. Rockwood (EDIS, 2007)
Circular 1516, a 5-page paper by Matthew Langholtz, Douglas R. Carter, and Donald L. Rockwood, describes a decision support system that can be used to determine the economic viability of SRWC systems for use in Florida. Includes references. Published by the UF School of Forest Resources and Conservation, May 2007.